Diagnostic Effects of the External Environment on the Share Capital Structure of Ukrainian Auto Building Enterprises (Economic journal of Lesya Ukrainka Volyn National University, 2018)
Automotive industry is a powerful source of scientific and technological progress at the expense of high-tech and high-tech production, socio-economic country growth of the, as it creates tens of thousands of jobs to provide a new quality of life for its citizens, a powerful impetus for the development of other sectors of the country’s machine-building complex and related industries. With such enormous potential, obtaining the status of an automobile country is an extremely difficult task, as the development of automobile engineering requires very large financial, scientific, intellectual and managerial resources. The present state and trends of the domestic automotive industry development are explored; Using PEST analysis, external factors are identified which have the greatest influence on the structure of the share capital of domestic automobile construction enterprises; ways of neutralizing the influence of negative external factors on the activity of Ukrainian automobile construction companies were suggested.In order, to level the influence of negative environmental factors on the automobile manufacturing enterprises of Ukraine and get out of the crisis, the first and most important stage should be to unite the efforts of the state and domestic joint-stock companies, attract foreign investment by creating joint ventures with a share in the share capital of global automotive companies, and funds for support of this activity should be financed from the national budget, through investment income, as well as own auto finance edpriyaty. However, in order to be solvent and capable of joint activities, domestic joint-stock enterprises must first of all increase their investment attractiveness in the market, which directly depends on the efficiency of the capital structure.
Keywords: share capital, efficiency of structuring of share capital, PEST analysis, external factors, loan financing sources of capital, debt restructuring, investment attractiveness.